THE ROLE OF INDIGENOUS KNOWLEDGE SYSTEMS IN ADDRESSING INTERGENERATIONAL TRAUMA: A STUDY OF INDIGENOUS COMMUNITY-BASED INITIATIVE - Ompha Mpilo; Decent Munzhelele; Shine Chauke (CV. RADJA PUBLIKA, 2025)
This study explores the role of Indigenous knowledge systems in addressing intergenerational trauma through community-based initiatives, using a qualitative research approach with an exploratory design. Employing a comprehensive desktop methodology, the research draws on a wide range of secondary sources, including academic literature, reports, and case studies of Indigenous-led healing initiatives. The data was analyzed thematically to identify key patterns and insights related to the effectiveness of Indigenous knowledge in healing trauma across generations. The findings highlight the significance of cultural revitalization, identity restoration, collective healing, and the pivotal role of elders in transferring intergenerational knowledge. The study also emphasizes the holistic nature of Indigenous healing, which integrates physical, mental, emotional, and spiritual well-being. Despite the barriers to integrating Indigenous knowledge into mainstream healing practices, including institutionalized marginalization and cultural misunderstanding, the research demonstrates how land-based practices and community solidarity contribute to resilience and empowerment. The study concludes that Indigenous knowledge systems offer profound insights into trauma recovery, promoting a culturally grounded approach that can enhance contemporary healing efforts and address the ongoing effects of colonization.